First detection of Leishmania DNA in Lutzomyia longipalpis sensu lato (Diptera: Phlebotominae) in southem Mexico - Ana C Montes de Oca-Aguilar; Edith A Fernández-Figueroa; Mariela I Pavón-Méndez; Karina López-Ávila; Erika I Sosa-Bibiano; Eduardo A Rebollar-Téllez; Jorge A Palacio-Vargas; Haydee Miranda-Ortíz; Elsy N Loría-Cervera (Journal of Vector Borne Diseases, 2023)
Background & objectives: Lutzomyia longipalpis sensu lato is an important vector of Leishmania infantum, the causative agent of visceral leishmaniasis (VL) in Latin America. In Mexico, this species has been recorded in endemic areas of leishmaniasis transmission, but it has never been detected as infected with Leishmania sp. This study aimed to explore the presence of Leishmania DNA in Lutzomyia longipalpis s.l. from samples collected with a human baited trap from an endemic region of leishmaniasis in southeastern Mexico. Methods: This is a prospective study where a total of 45 specimens of Lu. longipalpis s.l. collected in two sites of Yucatan state with records of leishmaniasis were tested. The nuclear ribosomal Internal Transcribed Spacer was amplified for the detection of Leishmania DNA. Results: Two females were positive for Leishmania DNA. None of the specimens positive for parasite DNA were found fed or gravid. Our finding represents the first record of infection by Leishmania in Lu. longipalpis s.l. for the country. Interpretation & conclusion: More studies are necessary to understand the potential role of this vector species in the transmission cycle of the causative agent of leishmaniasis in the southeastern and other regions of Mexico.